2007
DOI: 10.1210/en.2007-0459
|View full text |Cite
|
Sign up to set email alerts
|

High Basal Levels of Functional Toll-Like Receptor 3 (TLR3) and Noncanonical Wnt5a Are Expressed in Papillary Thyroid Cancer and Are Coordinately Decreased by Phenylmethimazole Together with Cell Proliferation and Migration

Abstract: High basal levels of TLR3 and Wnt5a RNA are present in papillary thyroid carcinoma (PTC) cell lines consistent with their overexpression and colocalization in PTC cells in vivo. This is not the case in thyrocytes from normal tissue and in follicular carcinoma (FC) or anaplastic carcinoma (AC) cells or tissues. The basally expressed TLR3 are functional in PTC cells as evidenced by the ability of double-strand RNA (polyinosine-polycytidylic acid) to significantly increase the activity of transfected NF-kappaB an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
93
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(104 citation statements)
references
References 73 publications
8
93
0
Order By: Relevance
“…The significance of this finding is unknown; however, TLR3 and Wnt-5a are coordinately expressed in certain tumor lines which have undergone malignant transformation [17,18] but not in benign tumors. Chronic inflammation within the pancreas is thought to contribute to the increased prevalence of pancreatic cancer in persons with T2DM [23,24] .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The significance of this finding is unknown; however, TLR3 and Wnt-5a are coordinately expressed in certain tumor lines which have undergone malignant transformation [17,18] but not in benign tumors. Chronic inflammation within the pancreas is thought to contribute to the increased prevalence of pancreatic cancer in persons with T2DM [23,24] .…”
Section: Discussionmentioning
confidence: 98%
“…The Wingless (Wnt) family of secreted glycoproteins control early developmental processes including cellular migration, differentiation, and proliferation but are also involved in oncogenesis and tumor spread [16] . Recently, we demonstrated that high basal expression of TLR3 and Wnt5a are coordinately expressed in tumors that have undergone malignant transformation and their determination immunohistochemically might serve as a diagnostic marker [17,18] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been shown recently that high basal levels of Toll-like receptor 3 (TLR3) and noncanonical WNT5a RNA are present in PTCs cell lines consistent with their overexpression and colocalization in PTC cells in vivo, and that the basally expressed TLR3 are functional in PTC cells, as evidenced by the ability of double-strand RNA (polyinosine-polycytidylic acid) to increase significantly the levels of the end product of TLR3 signaling CXCL10 (McCall et al 2007).…”
Section: Introductionmentioning
confidence: 91%
“…This induces proinflammatory cytokine secretion (IL6 and IL1), antiapoptotic factors (Bcl-XL, cIAP1, ABL), as well as, pro-angiogenic factors expression (VEGF). High expression of TLR3 has been reported in a papillary thyroid cancer cell line which is consistent with its overexpression in human papillary thyroid cancer in vivo [5]. As one of the main mediator of lipopolysaccharide action, the lack or overexpression of TLR4 has also been associated with aggressive follicular thyroid cancers [6].…”
mentioning
confidence: 56%